2010
DOI: 10.1016/j.juro.2010.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Patient Radiation Exposure During Percutaneous Nephrolithotomy

Abstract: Patients with higher body mass index, greater stone burden, nonbranched stones and multiple nephrostomy access tracts are at risk for increased radiation exposure during percutaneous nephrolithotomy. Urologists must seek alternative strategies to minimize radiation exposure, such as tighter collimation to the region of interest, judicious use of magnification and the acquisition of as few images as possible during stone removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 20 publications
3
45
1
Order By: Relevance
“…The median BMI of our study population is within the reported range in our geographic area 23 and is comparable to similar PCNL studies reporting BMI. 15,19,20,24 The mean fluoroscopy time in our study cohort was only 3.4 minutes, which is shorter than most case series using standard PCNL techniques (Table 4), and the mean effective dose of 2.4 mSv in our cohort compares favourably to published reports. For standard PCNL using contrast pyelography, Lipkin and colleagues 24 reported a mean fluoroscopy time about 3 times the amount in our study cohort.…”
Section: Tion Exceed the International Commission On Radiologicalsupporting
confidence: 64%
See 2 more Smart Citations
“…The median BMI of our study population is within the reported range in our geographic area 23 and is comparable to similar PCNL studies reporting BMI. 15,19,20,24 The mean fluoroscopy time in our study cohort was only 3.4 minutes, which is shorter than most case series using standard PCNL techniques (Table 4), and the mean effective dose of 2.4 mSv in our cohort compares favourably to published reports. For standard PCNL using contrast pyelography, Lipkin and colleagues 24 reported a mean fluoroscopy time about 3 times the amount in our study cohort.…”
Section: Tion Exceed the International Commission On Radiologicalsupporting
confidence: 64%
“…18 Increased radiation exposure during PCNL has been correlated with high BMI, larger stone burden, longer operative times and surgeon inexperience. [19][20][21] In our study, longer fluoroscopy time correlated with increased stone size (p < 0.01), longer operative time (p < 0.01) and lower treatment success rates (p < 0.01); these factors may be considered surrogate markers of the degree of surgical difficulty. However, higher effective dose, a more accurate measure of biologically significant radiation exposure than fluoroscopy time alone, 16,22 correlated only with increased skin-to-stone distance (p < 0.01); interestingly, we did not find any correlation between BMI and ePCNL-related fluoroscopy time, effective dose or operative time as commonly reported in other studies involving standard PCNL techniques.…”
Section: Tion Exceed the International Commission On Radiologicalmentioning
confidence: 48%
See 1 more Smart Citation
“…Although surgeon's preferences determine the imaging method choice, fluoroscopy and ultrasounds are the most common imaging technologies for puncture guidance and planning 2,21 . X-ray exposure, 2D image, difficult visualization of small calculi, operator dependence and requirement of skill has been reported as the main limitations associated with these imaging techniques 2,7,8,22 .…”
Section: Discussionmentioning
confidence: 99%
“…13,15,24 Although real-time images may facilitate the puncture step by providing a visualization of the target and surgical instruments, the use of CT and fluoroscopy are limited by the exposition of ionizing radiation and its associated risks. 34 Mancini and colleagues 35 reported higher body mass index, greater stone burden, nonbranched stones, and multiple nephrostomy access tracts as the main aspects for increased radiation exposure during PCNL.…”
Section: 15mentioning
confidence: 99%